(3GdeSFhdjI GdSjGSjI GdhRGQjI CeGe GdHQdeGf habG ddOSJhQ GdchjJj (B: s (3OQGSI ebGQfI(B-(3bWQ(B-(3GdHMQjf (B/ s - (3NGdO aGjR GdaGjR GdYLeis; (3jMji GdLeds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2012)
(3gOa GdHGMK aj OQGSJg GdJi YfhGfgG GdeSFhdjI GdSjGSjI GdhRGQjI CeGe GdHQdeGf habG ddOSJhQ OQGSI ebGQfI (B"(3bWQ(B-(3GdHMQjf(B" (3Gdhbha Ydi GdeSFhdjI GdSjGSjI GdhRGQjI HTcd YGe h ai OhdI GdchjJ HTcd NGU eY HjGf TQhWgG h ELQGAGJgG h GdCKGQ GdJi JJQJH YdjgG(B. (3h GSJNOe GdHGMK GdefgL GdhUai GdJMdjdj h GdefgL GdebGQf(B. (3h LGAJ GdOQGSI aj COhGJ GdQbGHI GdHQdeGfjI(B: (3GdebUhO HGdeSFhdjI GdSjGSjI GdhRGQjI h CgejJgG h MOhOgG(B: (3GdeSFhdjI GdSjGSjI GdhRGQjI CeGe GdHQdeGf aj cd ef GdchjJ h GdHMQjf h bWQs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2012s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B425-440s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdYGes; (3GdQbGHI GdHQdeGfjIs; (3GdeSFhdjI GdSjGSjI GdhRGQjIs; (3eLdS GdCeI GdchjJis; (3GdeSFhdjI GdLfGFjIs; (3GdeSFhdjI GdSjGSjI GdNGdUIs; (3GdeSFhdjI GdLfGFjI GdSjGSjIs; (3WQM GdKbIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes